Online Learner Engagement in Higher Education: Part 2 - Practice - Brad Bell (Ömer Gökhan Ulum, 2023)
Online learner engagement is a key factor for the quality and effectiveness of online education. It refers to the degree of involvement, participation, and interest that students show in their online courses and how they interact with the content, the instructor, and their peers. However, engaging online learners can be challenging due to the lack of physical presence, social cues, and immediate feedback that are often present in face-to-face settings. Therefore, it is important for online educators and researchers to understand the factors that influence online learner engagement and the educational techniques that can enhance it. This paper discusses the factors that influence online learner engagement, such as technology and interface characteristics, content area experience, student roles and instructional tasks, information overload, transactional distance, e-learning capital, perceived usefulness, computer self-efficacy, motivational beliefs, and learning strategies. It also reviews the educational techniques that can enhance online learner engagement, such as social engagement, cognitive engagement, behavioral engagement, collaborative engagement, and emotional engagement. Moreover, it explores the gamification and simulation techniques that can also enhance online learner engagement by providing interactive and immersive learning experiences. Finally, it examines the methods and instruments for measuring online learner engagement, such as self-reports, behavioral logs, physiological measures, learning analytics, observation and feedback, and various scales and surveys. The paper concludes with a summary of the main findings and implications for online education practice and research, and identifies some gaps in the existing literature and suggests some directions for future research.